The Causes and Consequences of South Asia's Nuclear Tests - Synnott, Hilary (Karachi, Pakistan Oxford University Press, 2001)
The nuclear tests by India and Pakistan in May 1998 shook the region and challenged the near-global consensus on non-proliferation. In their wake, the region's underlying problems have become still more intractable, and the need to resolve them has become more urgent than ever. The international community has been powerless in its response, and a new approach is now called for. Political stability should be encouraged within the countries concerned, in their relations with each other and in the wider region. Arms control and measures to increase confidence and security need to be re-examined and adapted to the changed circumstances. The nuclear-weapon states themselves should look again at their attitudes towards arms-control instruments, while India and Pakistan need to reappraise or clarify their nuclear doctrines, and take steps to improve relations.
Include Appendix and Notes
Keywords: Military policy -- Nuclear weapons -- Nuclear weapons--Testing -- Pakistan -- India -- South Asia